Earned Value Management Analysis of Construction Service Unit Price Contract: A Case Study at PT. XYZ - I Putu Artama Wiguna; Dio Dhany Prasetyo (Journal Research of Social Science, Economics, and Management, 2025)
Achieving projects on time and within budget is critical for PT. XYZ to meet its work plan and production targets. The company undertakes massive, simultaneous development projects, requiring effective project management to prevent sharp production declines. Projects executed under unit-price Construction Service Contracts must be closely monitored in terms of scope, schedule, and cost. Moreover, these contracts entail long lead times (~6 months from tender to contractor mobilization), so early and accurate duration estimates are essential to avoid contractor unavailability. This study applied Earned Value Management (EVM) to integrate scope, time, and cost data for forecasting project completion. Three EVM-based schedule forecasting methods were compared: Planned Value (PV), Earned Duration (ED), and Earned Schedule (ES). Five well development projects (A–E) were analysed as case studies. The results show that PV and ED provided the most accurate duration forecasts. PV was consistently the top performer, with very low mean absolute percentage error (MAPE) for projects A, B, and C (0.3–1.2%). While PV’s accuracy dropped for the delayed projects D (35.5% error) and E (9.4%), its forecasts were still far more accurate than those from ES. The ED method was also reliable (MAPE < 12% for A–C) and showed a similar decline in accuracy for projects D and E.